2012
DOI: 10.1038/bjc.2012.186
|View full text |Cite
|
Sign up to set email alerts
|

Lower treatment intensity and poorer survival in metastatic colorectal cancer patients who live alone

Abstract: Background:Socioeconomic status (SES) and social support influences cancer survival. If SES and social support affects cancer treatment has not been thoroughly explored.Methods:A cohort consisting of all patients who were initially diagnosed with or who developed metastatic colorectal cancer (mCRC, n=781) in three Scandinavian university hospitals from October 2003 to August 2006 was set up. Clinical and socioeconomic data were registered prospectively.Results:Patients living alone more often had synchronous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 33 publications
1
40
1
Order By: Relevance
“…Socioeconomic factors [1921], less access to health care, high-risk sexual practices [22,23], host immunity/genetics [24], and tobacco and alcohol consumption[25, 26] have all been linked to racial differences [18]. However the reason for racial disparities between incidence and outcome is still not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic factors [1921], less access to health care, high-risk sexual practices [22,23], host immunity/genetics [24], and tobacco and alcohol consumption[25, 26] have all been linked to racial differences [18]. However the reason for racial disparities between incidence and outcome is still not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Another 288 persons were excluded because of a cancer diagnosis prior to the survey date in 1985. Since the method used to identify network types in this sample was previously validated in the Jewish population [15], the current study focused only on the Jewish respondents (n = 3679).…”
Section: Study Populationmentioning
confidence: 99%
“…Ethnic origin was categorized into four groups by continent of birth: Europe, North Africa, Africa, Asia and Israeli born (reference group). Five distinct social networks were defined among the survey population by means of cluster analysis that was based upon a previously published methodology [15].…”
Section: Variable Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such social support may impact outcomes among patients. Indeed, a recent study found that patients’ living alone more often had synchronous metastases at presentation and were less often treated with combination chemotherapy than those cohabitating [14]. …”
Section: Discussionmentioning
confidence: 99%